Implementation Lessons from Six Early Head Start - Child Care Partnerships. Issue 8 (17th November 2019) - Halle, Tamara; Banghart, Patti; Zaslow, Martha; Cook, Maya; Kane, Maggie; Bartlett, Jessica Dym; Redd, Zakia; Bamdad, Tiffany; Cox, Alexandra; Lloyd, Chrishana M.
ABSTRACT: Research Findings : This study examined the development and implementation of six Early Head Start Child Care Partnerships (EHS-CCPs), unique collaborations between EHS grantees and community-based child care partners that expand access to high-quality child care and comprehensive services for low-income infants, toddlers, and their families. Interviews and focus groups with 111 key informants identified similarities across the six EHS-CCPs in initial outreach to community partners for establishing partnerships and approaches to developing partnership agreements but variation in approaches to monitoring quality improvement activities. Benefits and challenges to partnerships for programs and families were noted. Practice or Policy : Findings suggest a need for additional guidance for EHS-CCPs on key components of implementation, including the partnership agreement process, monitoring quality improvement plans, offering support for meeting program requirements, and providing comprehensive services. For example, five of the six partnerships reported the EHS grantee led the development of their partnership agreements. While this approach was attributed to child care partners' lack of prior experience in developing agreements, further guidance on how to engage partners collaboratively in an agreement process that better emulates the principles of authenticity and equality from the conceptual framework for collaborations in early care and education would be useful.